LICENCIATURA EM EDUCAÇÃO DO CAMPO NA UNIVERSIDADE FEDERAL DO ESPÍRITO SANTO: UM ESTUDO DE CASO COM ESTUDANTES EGRESSOS E EGRESSAS - Sobrinho, Eliana de Deus (2022)
This research is part of the production of the Research Group (CNPq) “Cultures, Partnerships and Rural Education” of the Graduate Program in Education (PPGE) of the Education Center (CE) of the Federal University of Espírito Santo (UFES), in the Research Line Teaching, Curriculum and Cultural Processes, with the objective of analyzing the pedagogical praxis of graduates of the Degree in Rural Education (LEdoC). The problem to be investigated is: What learnings obtained in the Degree in Rural Education are evidenced in the pedagogical praxis of the graduates? We will work with the following theoretical references: Gramsci (1991) to help us with the concepts of organic intellectuals; Freire (1979, 1987, 2014) contributes to discussions on education, dialogue, culture, teacher training and pedagogical praxis; Brandão (1983) and Arroyo (2004) collaborate with the concepts of education, dialogue and culture; Ludke and André (1986) collaborate with the methodology, with regard to the case study; Caldart (2002, 2010, 2011) and Molina (2002, 2011, 2014) to discuss and analyze Rural Education and the Degree in Rural Education; Foerste (2005 and 2013) to conduct reflections on inter-institutional partnerships and Gerke (2014, 2018) reinforces the analysis on the training of rural teachers. In this research, we opted for a qualitative approach, as presented by Ludke and André (1986). It will be carried out from a case study, having as research locus the municipal education network of Domingos Martins/ES and the subjects of the research will be the students graduating from the Degree in Rural Education, from their relations with the school and the community where they practice. The results obtained in the course of this study, indicate that the graduates of LEdoC/UFES are anxious for a public contest to act and develop their activities in Escolas do Campo. These subjects aim to transform the school and contribute to the Licentiate course to train not only “teachers”, but “educators” in the countryside. Their speeches demonstrate some principles of initial training in their praxis, especially with regard to collective work, where they abandon the previous practice of individual work, interdisciplinary practice and research. But they still cannot put into practice training by area of knowledge, as they were trained in a logic to confront a compartmentalized organization of disciplines and, in practice, teaching networks are organized into specific disciplines.